2021
DOI: 10.1063/5.0062787
|View full text |Cite
|
Sign up to set email alerts
|

On-demand cold plasma activation of acetyl donors for bacteria and virus decontamination

Abstract: Antibiotics are commonly used as the first line of defense in the treatment of infectious diseases. However, the rise of antimicrobial resistance (AMR) is rendering many antibiotics less effective. Consequently, effective non-antibiotic antimicrobial strategies are urgently needed to combat AMR. This paper presents a strategy utilizing cold plasma for the "on-demand" activation of acetyl donor molecules. The process generates an aqueous-based antimicrobial formulation comprising a rich mixture of highly oxidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…During the editorial submission of this manuscript Szili et al 30 reported the inhibition of SARS-CoV-2 infectivity with two acetyl donors (TAED and pentaacetate glucose) present in an aqueous solution that was activated with cold plasma (PA-TP). PA-TP medium contains peracetic acid in addition to RONS or and was able to reduce the virus loads in higher percentages with respect to a distilled water activated control (PA-DIW).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the editorial submission of this manuscript Szili et al 30 reported the inhibition of SARS-CoV-2 infectivity with two acetyl donors (TAED and pentaacetate glucose) present in an aqueous solution that was activated with cold plasma (PA-TP). PA-TP medium contains peracetic acid in addition to RONS or and was able to reduce the virus loads in higher percentages with respect to a distilled water activated control (PA-DIW).…”
Section: Discussionmentioning
confidence: 99%
“…Although CAPs and PAMs share the same active principle of oxidative stress, PAMs have an interesting complementary advantage respect to CAPs: its capability to reach body cavities that are inaccessible for CAPs applicators systems. The possibility ot use PAMs against SARS-Cov-2 has only been recently proposed by experiments with virus and isolated pseudo-virus 30 , 31 and its capability to be applied on living cells and complex body cavities had inspired our work. In this paper we show in-vitro experiments demonstrating the vulnerability of SARS-CoV-2 and PR8 H1N1 influenza A virus to PAMs with a minimal or neglectable damage to healthy cells with especial emphasis on non-inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%
“…Promising outcomes of CAP have been demonstrated, with several recent studies establishing its efficacy against planktonic microorganisms and testing its anti-biofilm activity [ 14 , [16] , [17] , [18] ]. In regards to skin and wounds, a number of studies have focused on singular bacteria, such as Pseudomonas aeruginosa and Staphylococcus aureus [ [19] , [20] , [21] , [22] , [23] , [24] ], whilst CAP has also been shown to possess inhibition effects against fungi such as dermatophytes [ 25 ] and C. albicans [ 13 , 15 , 26 ]. At a mixed species level, there is evidence of CAP efficacy against a biofilm containing S. aureus and C. albicans [ 27 ], and S. aureus with P. aeruginosa and Enterococcus faecalis [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…. [21][22][23][24][25] These reactive species have received increased attention regarding their prominent bactericidal effects. [26][27][28] The bactericidal efficiency of ONOO − in vitro was also validated by Liu et al and Zhang et al [20,24] Most importantly, ONOO − is protonated upon contact with the pericarp and decomposes rapidly within seconds.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] As an important antimicrobial specie of the human immune system, ONOO − is able to cross cell membranes and can react with most biological molecules, either by direct oxidation or indirectly by decomposing into highly reactive radicals, such as O2 ${{\rm{O}}}_{2}^{\bullet -}$, •OH, O21 ${}^{1}{\rm{O}}_{2}$. [ 21–25 ] These reactive species have received increased attention regarding their prominent bactericidal effects. [ 26–28 ] The bactericidal efficiency of ONOO − in vitro was also validated by Liu et al and Zhang et al [ 20,24 ] Most importantly, ONOO − is protonated upon contact with the pericarp and decomposes rapidly within seconds.…”
Section: Introductionmentioning
confidence: 99%